Validity of Covernote Issued by Notary in Certificate Guarantee at Bank - Avicena, Yusnika (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to determine and analyze the validity of covernotes issued by notaries in guaranteeing certificates in banks and legal protection for banks and customers in the event of default in the use of covernotes as credit guarantees. The research approach method used in this thesis is the normative legal research method. The specifications of this study use descriptive analysis. The types of data used in this study are primary legal materials including the 1945 Constitution, the Civil Procedure Law, Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 concerning Banking, Law No. 4 of 1996 concerning Mortgage Rights, Law No. 8 of 1999 concerning Consumer Protection, Law No. 42 of 1999 concerning Fiduciary Guarantees, Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary, as well as secondary legal materials containing books, journals, and other supporting documents. Tertiary legal materials contain the Great Dictionary of the Indonesian Language, Encyclopedia. Data collection using literature study techniques. The data analysis method used in analyzing the data is qualitative analysis. The results of the study indicate that the validity of the covernote as a credit guarantee by the bank is only as a temporary guarantee. Covernote is not evidence of collateral, only a statement issued by a notary due to urgent interests, and is always made by a notary based on the customs in issuing deeds or certificates that are still in the process such as mortgage certificates. And if a problem occurs, the bank can make a claim for the return of receivables from the debtor through mediation or filing a lawsuit in court. Legal protection for creditors and customers in the event of a default in the use of covernotes as credit guarantees is regulated in Article 1 paragraph (1) No. 8 of 1999 concerning the Consumer Protection Law, Legal protection for creditors is regulated in Article 11 of Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 concerning Banking.